Cortical and subcortical activities during food rewards versus social interaction in rats - Florbela Rocha-Almeida; Ana R. Conde-Moro; Antonio Fernández-Ruiz; José M. Delgado-García; Agnès Gruart (Scientific Reports)
Abstract Balancing food foraging with social interaction is crucial for survival and reproduction in many species of mammals. We wanted to investigate the reward preferences in adult male rats by allowing them to lever-press for both food and social rewards (interaction with another rat), while their performance and electrophysiological activities were recorded. Local field potentials (LFPs) were analyzed across five neuroanatomical regions involved in reward processing, decision-making, and social behavior. Despite ad libitum food availability, rats consistently prioritized food. LFP analysis revealed a decrease in nucleus accumbens (NAc) spectral power following social interaction, accompanied by specific alterations in delta and theta bands within the medial prefrontal cortex (mPFC). The spectral power of LFPs delta and/or theta bands were different for the five selected regions following food reward vs. social interactions. Cross-frequency coupling analysis provided further insights, demonstrating dynamic changes in theta-to-gamma coupling during both food and social rewards, with distinct roles for slow- and fast-gamma frequencies. These findings shed light on the intricate neural processes underlying reward preferences and/or decision-making choices, highlighting the NAc’s potential role in social reward processing, and the mPFC’s involvement in modulating theta–gamma rhythms during reward-related decision-making.